1982
DOI: 10.2527/jas1982.553543x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Environmental and Phenotypic Relationships among Gestation Length, Birth Weight, Growth Traits and Age at First Calving in Beef Cattle

Abstract: Data on the Red Angus, Angus and Hereford herds of Pioneer Hi-Bred International, Inc., Des Moines, Iowa, collected from 1968 to 1976, were analyzed for relationships among gestation length, birth weight, prenatal gain (birth weight adjusted for gestation length), growth traits and age at first calving. A total of 5,691 calf records, 1,783 listing gestation length, were included in the study. Paternal half-sib analyses and least-squares procedures were used to compute heritability estimates and genetic, enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
58
5
3

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 9 publications
(12 reference statements)
13
58
5
3
Order By: Relevance
“…The estimates reported by Everett and Magee (1965), Burfening et al (1981), and Bourdon and Brinks (1982) generally concur with Koch's averages but still show variety. Brown and Galvez (1969) disagreed slightly from Vesely and Robison (1971) report variances for direct effect that were higher than most others reviewed.…”
Section: Parameter Estimates Birth Weightsupporting
confidence: 76%
See 3 more Smart Citations
“…The estimates reported by Everett and Magee (1965), Burfening et al (1981), and Bourdon and Brinks (1982) generally concur with Koch's averages but still show variety. Brown and Galvez (1969) disagreed slightly from Vesely and Robison (1971) report variances for direct effect that were higher than most others reviewed.…”
Section: Parameter Estimates Birth Weightsupporting
confidence: 76%
“…From the values in Table 1, the conclusion is drawn that relatively higher proportion of direct than maternal variance exists for birth weight, agreeing with general conclusions of Bourdon and Brinks (1982). They concluded that direct effects for birth weight account for three to four times more variation than do maternal effects.…”
Section: Parameter Estimates Birth Weightsupporting
confidence: 75%
See 2 more Smart Citations
“…Vários trabalhos relatam correlação positiva entre DG e PESNAS (Lôbo et al, 2000), indicando que a duração de gestação mais longa está associada a maior peso ao nascer, conseqüentemente maior DG estaria ligada à maior dificuldade de parto (McGuirk et al, 1999). São poucos os resultados encontrados sobre correlação entre DG e outras características de desempenho ponderal, mas alguns deles diferem do que foi obtido no presente estudo, ao apresentarem correlação negativa entre DG e peso à desmama, peso a um ano, ganhos de peso do nascimento à desmama, da desmama a um ano e na pós-desmama (Bourdon & Brinks, 1982). Pelos resultados obtidos pode-se supor que a seleção para PESDES, PESSOB e GP345 resultaria em aumento da DG e do PESNAS.…”
Section: Resultsunclassified